In vitro Propagation of Leucas biflora (Vahl) Sm. - A Vulnerable Medicinal Herb (Plant Tissue Culture and Biotechnology, 2024)
A rapidly well-developed in vitro regeneration system has been established for Leucas biflora using nodal segments as explants and MS medium supplemented with various concentrations and combinations of plant growth regulators (PGRS). MS medium containing 2.0 mg/l BAP and 0.5 mg/l NAA showed the highest response (95.99%) in induction of shoot buds. This media combination also produced the maximum number (11.20 ± 0.49) of multiple shoot bud per explant after 3 subcultures at an interval of 14-days. Microshoots showed the maximum elongation (4.70 ± 0.07 cm) in the same medium along with subcultures. These elongated shoots were further grown on rooting media, producing vigorous and healthy root systems. The best response (95.99 ± 1.63%) for rooting was obtained when half-strength MS medium was supplemented with 0.5 mg/l IAA + 0.5 mg/l IBA in 21 days of culture. In this combination, the average number and length of roots were 5.20 ± 0.33 and 4.80 ± 0.30 cm, respectively. The seedlings were removed from culture tubes and transplanted into the pots via several stages of acclimatization. Finally, 98% of the seedlings were found to survive under natural condition.Plant Tissue Cult. & Biotech. 34(1): 49-54, 2024 (June)